Thermally induced spin-crossover in the Fe(3-ethynylpyridine)2[M(CN)4] series with M = Ni, Pd, and Pt. The role of the electron density found at the CN 5σ orbital. (4th May 2022) - Terrero, R.; Avila, Y.; Mojica, R.; Cano, A.; Gonzalez, M.; Avila, M.; Reguera, E.
Abstract : The charge density accumulated at the CN 5σ orbital, via π-back bonding interaction, determines the crystal field splitting for the Fe(ii ) atom and the temperature where the spin transition is observed. Abstract : A series of 2D coordination polymers show thermally induced spin-crossover where the temperature for the spin transition, according to the SQUID magnetic data, follows the order Ni < Pd < Pt. A similar order is observed from the enthalpy change (Δ H ) during the spin transition, obtained from DSC curves. Both the magnetic and DSC measurements show a similar hysteresis. The thermally induced spin transition was also monitored using IR and Raman spectra, with the ν (CN) frequency probing the spin transition in the iron atom. These three coordination polymers crystallize with an orthorhombic unit cell, in the P 21 21 2 space group (Nr. 18). For Ni and Pd, the crystal structure was solved and refined from powder XRD patterns and calculated using a periodic DFT algorithm implemented in the VASP software package for Pt. Information on the structure for the LS phase in the series was derived from analog calculations by relaxing the structure for the HS phase. The observed order for the spin transition temperature was rationalized in terms of electron density found at the CN 5σ orbital, which determines the Fe–NC bond strength. Such electron-density results from the M → CN π-back bonding interaction. This interaction subtracts charge from the inner metal (M) and accumulates it at that orbital. The N1s core-level binding energy, which is obtained using the corresponding XPS spectrum, probes that charge relocation. An excellent correlation was observed between the spin transition temperature and the N1s binding energy.